Dementia prevalence, a contextual factor associated with SARS‐CoV‐2 in veterans affairs community living centers. Issue 10 (29th June 2022) - Bayer, Thomas A.; DeVone, Frank; McConeghy, Kevin W.; Halladay, Christopher W.; Quach, Lien; Rajan, Ashna; Elhamamsy, Salaheldin; Cadieux, Marilyne; Singh, Mriganka; Sachar, Moniyka; Nanda, Aman; Gravenstein, Stefan; et al.
Abstract: Background: Alzheimer's disease and related dementias (ADRD) impact the diagnosis and infection control of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) in nursing homes (NH) by influencing the behavior of residents and their caregivers. Health system data show an association between ADRD and SARS‐CoV‐2. Whether this association is present in NH populations remains unknown. How increased SARS‐CoV‐2 risk among residents with ADRD impacts the greater NH population also remains unknown. Methods: This retrospective cohort study used electronic health record data on Veterans residing in 133 Veterans Affairs Community Living Centers (CLC) and 15 spinal cord injury units from March 1, 2020 to December 13, 2020. We measured ADRD using diagnostic codes 12 months before an index SARS‐CoV‐2 test date for each resident. We used Poisson regression to determine the relative risk of SARS‐CoV‐2 for the highest quartile of facility ADRD prevalence versus the lowest, stratifying by individual ADRD status, and adjusting for covariates, with and without a random intercept to account for facility clustering. Results: Across the study period, 15, 043 residents resided in CLCs, 1952 (13.0%) had SARS‐CoV‐2, and 8067 (53.6%) had ADRD. There was an estimated 60% increased risk of SARS‐CoV‐2 in facilities with highest dementia prevalence versus lowest (relative risk, 1.6 [95% confidence interval 0.95, 2.7]). Conclusions: CLC residents had a greater likelihood of SARS‐CoV‐2 infection in facilities with greater ADRD prevalence. Facility characteristics other than ADRD prevalence may account for this association.